EVALUACIÓN DE LA DIMENSIÓN DE LA ZONA SENSIBLE DE UN DETECTOR SEMICONDUCTOR COAXIAL DE GeHP - Gómez B., Javier (2004)
In this work the sensibility behavior of a coaxial GeHP detector is presented with respect to the arrival of a colhmated radiation beam in the frontal and lateral sides ofthe detector. The results show that for a horizontal or vertical configuration of the cryostat, a preferential direction of the detection exists. From the sensibility profiles, an estimate of the sensitive dimension of the semiconductor glass of the detector was obtained.